Effect of the R119G mutation on human P5CR structure and its interactions with NAD: Insights derived from molecular dynamics simulation and free energy analysis. (April 2017) - Sang, Peng; Xie, Yue-Hui; Li, Lin-Hua; Ye, Yu-Jia; Hu, Wei; Wang, Jing; Wan, Wen; Li, Rui; Li, Long-Jun; Ma, Lin-Ling; Li, Zhi; Liu, Shu-Qun; et al.
Graphical abstract: Highlights: Our computational results confirm the hypothesis in the study of Reversade et al. that a loss of or reduction in the binding affinity between NAD and P5CR might be an underlying cause of cutis laxa. Our study suggests that the R119G mutation affects the catalytic efficiency of P5CR by decreasing the kinetics of NAD entrance into the binding pocket and reducing the binding affinity between P5CR and NAD. Our study provides the first investigation of the interaction of P5CR and NAD by molecular dynamics simulation method. Abstract: Pyrroline-5-carboxylate reductase (P5CR), an enzyme with conserved housekeeping roles, is involved in the etiology of cutis laxa. While previous work has shown that the R119G point mutation in the P5CR protein is involved, the structural mechanism behind the pathology remains to be elucidated. In order to probe the role of the R119G mutation in cutis laxa, we performed molecular dynamics (MD) simulations, essential dynamics (ED) analysis, and Molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) binding free energy calculations on wild type (WT) and mutant P5CR-NAD complex. These MD simulations and ED analyses suggest that the R119G mutation decreases the flexibility of P5CR, specifically in the substrate binding pocket, which could decrease the kinetics of the cofactor entrance and egress. Furthermore, the MM-PBSA calculations suggest the R119G mutant has a lower cofactor binding affinity for NAD than WT. Our study provides insight into the possible role of the R119G mutation during interactions between P5CR and NAD, thus bettering our understanding of how the mutation promotes cutis laxa.